Effectiveness of a brief lay counsellor-delivered, problem-solving intervention for adolescent mental health problems in urban, low-income schools in India: a randomised controlled trial. (August 2020) - Michelson, Daniel; Malik, Kanika; Parikh, Rachana; Weiss, Helen A; Doyle, Aoife M; Bhat, Bhargav; Sahu, Rooplata; Chilhate, Bhagwant; Mathur, Sonal; Krishna, Madhuri; Sharma, Rhea; Sudhir, Paulomi; et al.
Summary: Background: Mental health problems are a leading cause of disability in adolescents worldwide. Problem solving is a well-tested mental health intervention in many populations. We aimed to investigate the effectiveness of a brief, transdiagnostic problem-solving intervention for common adolescent mental health problems when delivered by non-specialist school counsellors in New Delhi, India. Methods: This randomised trial was done in six government-run schools (three all-boys schools, two all-girls schools, and one co-educational school) that serve low-income communities. We recruited participants from grades 9 to 12 (ages 12–20 years) by selecting students with persistently elevated mental health symptoms accompanied by distress or functional impairment. Clinical eligibility criteria were assessed by research assistants using the Hindi-language version of the Strengths and Difficulties Questionnaire (SDQ), with reference to locally validated borderline cutoff scores of 19 or greater for boys and 20 or greater for girls on the SDQ Total Difficulties scale, an abnormal score of 2 or more on the SDQ Impact scale, and persistence of more than 1 month on the SDQ Chronicity index. Participants were randomly allocated (1:1) to problem solving delivered through a brief (2–3 week) counsellor-led intervention with supporting printed materials (intervention group), or problem solving delivered via printed booklets alone (control group). Primary outcomes were adolescent-reported mental health symptoms (SDQ Total Difficulties scale) and idiographic psychosocial problems (Youth Top Problems [YTP]) at 6 weeks. Primary analyses were done on an intention-to-treat basis at the 6-week endpoint. The trial is registered with ClinicalTrials.gov, NCT03630471 . Findings: Participants were enrolled between Aug 20, and Dec 4, 2018. 283 eligible adolescents were referred to the trial, and 251 (89%) of these were enrolled (mean age 15·61 years; 174 [69%] boys). 125 participants were allocated to each group (after accounting for one participant in the intervention group who withdrew consent after randomisation). Primary outcome data were available for 245 (98%) participants. At 6 weeks, the mean YTP scores were 3·52 (SD 2·66) in the intervention group and 4·60 (2·75) in the control group (adjusted mean difference –1·01, 95% CI –1·63 to –0·38; adjusted effect size 0·36, 95% CI 0·11 to 0·61; p=0·0015). The mean SDQ Total Difficulties scores were 17·48 (5·45) in the intervention group and 18·33 (5·45) in the control group (–0·86, –2·14 to 0·41; 0·16, –0·09 to 0·41; p=0·18). We observed no adverse events. Interpretation: A brief lay counsellor-delivered problem-solving intervention combined with printed booklets seemed to have a modest effect on psychosocial outcomes among adolescents with diverse mental health problems compared with problem-solving booklets alone. This counsellor-delivered intervention might be a suitable first-line intervention in a stepped care approach, which is being evaluated in ongoing studies. Funding: Wellcome Trust.